An analysis of post conflict economic & private sector performance - Burns, S (2022)
The liberal peacebuilding literature focuses on economic growth as a key factor to exiting the conflict trap. Yet, there is a lack of research, particularly in Africa, on private sector development in post conflict environments. This thesis uses the Structure- Conduct-Performance (Bain, 1959) framework, which suggests that conflict alters the conduct of economic decisions-makers, to analyse the private sector reconstruction process. This allows for the inclusion of non-mainstream critiques of peacebuilding in the analysis and view private sector development from a partially, “bottom-up” approach. Each of the three substantive chapters investigates different aspects of these relationships to determine how and why private sector performance is ultimately influenced by recent conflict. The first chapter provides analysis at a macroeconomic and country-level, determining the influence of foreign direct investment (FDI) and aid on economic growth within the post conflict period. Using a panel structural vector autoregressive model, this paper finds that on average, FDI per capita flows have a significant and positive impact on GDP, which is larger in magnitude than aid per capita. The second chapter uses firm-level data in the African continent to explore differences in what influences business growth in post conflict firms. The variations I find are i) employee training has a significant higher correlation with firm performance in post conflict regions and ii) foreign ownership and business networks only have a positive association with non-post conflict firm performance. Lastly, the final chapter of this thesis uses fifty qualitative interviews from Liberia to be used as a case study for private sector development in a post conflict African country. The evidence suggests that the conflicts experienced in Liberia had a profound and long-lasting effect on firm conduct (access to finance, human capital, innovation, and trust), which has had negative consequences on firm performance. However, different types of entrepreneurs and investors have effectively altered their conduct to navigate these post conflict barriers and survive the challenging business environment. Overall, this thesis provides novel evidence on private sector development in post conflict markets, which can ultimately contribute to reconstruction policy and programs in these regions.